2023
DOI: 10.1590/1806-9282.20230256
|View full text |Cite
|
Sign up to set email alerts
|

“Zooming” in the association between rosacea and fibromyalgia syndrome: ıs it worth mentioning?

Abstract: SUMMARY OBJECTIVE: We aimed to detect the frequency of fibromyalgia syndrome in patients with rosacea and determine whether this frequency was affected by the severity of rosacea and the quality of life. METHODS: In this prospective, controlled, cross-sectional study, a total of 94 consecutive rosacea cases and 87 age- and sex-matched controls were enrolled. The severity of rosacea was assessed in light of the findings of the National Rosacea Society Ethics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Acne dermal lesions, per se, are a chronic inflammatory disease of the skin of Homo sapiens which might lead to low self-esteem, anxiety, depression, and stigmatism which might frequently impair the quality of life seriously [11][12][13] . Mental effects may give rise to AV which might increase the risk of anxiety, depression, and suicide 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Acne dermal lesions, per se, are a chronic inflammatory disease of the skin of Homo sapiens which might lead to low self-esteem, anxiety, depression, and stigmatism which might frequently impair the quality of life seriously [11][12][13] . Mental effects may give rise to AV which might increase the risk of anxiety, depression, and suicide 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes, a fundamental aspect of rosacea, could influence neural pathways and contribute to headache development. Previous studies have reported a positive correlation between the duration and severity of rosacea and its inflammatory response [ 19 , 20 ]. In the current study, it was found that a majority of patients with headaches developed their headaches after being diagnosed with rosacea.…”
Section: Discussionmentioning
confidence: 99%